Mali grad Visokosrednjeveški grad v Kamniku = High Medieval Castle in Kamnik - Štular, Benjamin (Opera Instituti Archaeologici Sloveniae, 2009)
The in depth archaeological research of High Medieval castle presented in this book is unique in Slovenia and among just few in this part of Central Europe. The book is based on analysis of the archaeological data gathered in more than a decade of archaeological excavations in 1980s and 1990s.In the introductory chapter written sources and interpretative models are presented. The analysis of pictorial representations follows. The focus of the research is on the archaeological sources, though. Above all the analysis of the small finds, stratigraphy and spatial analysis of the castle itself and the castle in the landscape should be mentioned.